(untitled) (Clinics, 2021)
OBJECTIVES: Diagnosis and management of essential hypertension (EH) or type 2 diabetes mellitus (T2DM) by combining comprehensive treatment and classificatory diagnosis have been continuously improved. However, understanding the pathogenesis of EH patients with concomitant T2DM and subsequent treatment remain the major challenges owing to the lack of non-invasive biomarkers and information regarding the underlying mechanisms. METHODS: Herein, we collected 200 serum samples from EH and/or T2DM patients and healthy donors (N). Gene-expression profiling was conducted to identify candidate microRNAs with clinical significance. Then, a larger cohort of the aforementioned patients and 50 N were used to identify the correlation between the tumor suppressor miR-195-5p and EH and/or T2DM. The dual-luciferase reporter assay was used to explore the target genes of miR-195-5p. The suppressive effects of miR-195-5p on the 3′-UTR of the dopamine receptor D1 (DRD1) transcript in EH patients with concomitant T2DM were verified as well. RESULTS: Compared with that in other groups, serum miR-195-5p was highly downregulated in EH patients with concomitant T2DM. miR-195-5p overexpression efficiently suppressed DRD1 expression by binding to the two 3′-UTRs. Additionally, two single nucleotide polymorphisms, including 231T-A and 233C-G, in the miR-195-5p binding sites of the DRD1 3′-UTR were further identified. Collectively, we identified the potential clinical significance of DRD1 regulation by miR-195-5p in EH patients with concomitant T2DM. CONCLUSIONS: Our data suggested that miR-195-5p circulating in the peripheral blood served as a novel biomarker and therapeutic target for EH and T2DM, which could eventually help address major challenges during the diagnosis and treatment of EH and T2DM.